Social Relations & Humanitarian Qualities in Damascus Folk Proverbs- A Study in Vocabularies & Structures for Employment in Teaching Arabic for Non- Native Speakers - Alahmad, Hasan; Alumari, Samar (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The present study aims at monitoring social relations vocabularies, humanitarian qualities and their structures mentioned in Damascus folk proverbs so that they can be presented to non-native learners of Arabic, through two content analysis forms designed for this purpose. The sample of this study contains all the proverbs mentioned in Shami proverbs book “ Dictionary Of Parables in Al- Sham Damascus” written by Nizar Abaza, the 2nd edition , 2008. It contains about 3500 proverbs. Some of the results of this study are presented in the following points. First, the number of social relations vocabularies and their structures are 115 with 679 frequencies. The included domains are arranged in a descending way: family relations 55.37%, social environment 15.02%, professions 15.02% and social divisions 14.85%. Second, the number of human qualities vocabularies and their structures are 120 with 354 frequencies. The included domains are arranged in a descending way: negative social qualities 42.37%, negative physical qualities 25.14%, positive social qualities 18.64%, negative emotional situations 11.86%, positive physical qualities 7.62% and positive emotional situation 11.86%. The research also provided a model of how to use these vocabularies and structures in the teaching of Arabic for non- native speakers, and the model is directed to learners of the middle intermediate level in the skill of speech. يهدف البحث إلى رصد ألفاظ العلاقات الاجتماعيّة والصّفات الإنسانيّة وتراكيبهما الواردة في أمثال دمشق الشّعبيّة لتوظيفها في تعليم العربيّة للنّاطقين بغيرها، من خلال استمارتي تحليل محتوى صُمِّمتا لهذا الغرض، وقد اشتملت عينة البحث على جميع الأمثال الواردة في كتاب الأمثال الشّاميّة (قاموس أمثال العوامّ في دمشق الشّام) لنزار أباظة في طبعته الثّانية 2008م، وقد قارب عدد الأمثال فيه 3500 مثلٍ. ومن النّتائج التي توصَّل إليها البحث: بلغ عدد ألفاظ العلاقات الاجتماعيّة وتراكيبها (115) لفظاً وتركيباً، بمجموع تكراراتٍ وصل إلى (679) تكراراً، ورُتِّبت المحاور التي تضمّها تنازلياً على النّحو الآتي: العلاقات العائليّة (55.37%)، المحيط الاجتماعي (15.02%)، المهن (15.02%)، التَّقسيمات الاجتماعيّة (14.85%). وبلغ عدد ألفاظ الصّفات الإنسانيّة وتراكيبها (120) لفظاً وتركيباً، بمجموع تكراراتٍ وصل إلى (354) تكراراً، ورُتِّبت المحاور التي تضمّها تنازلياً على النَّحو الآتي: صفات اجتماعيّة سلبيّة (42.37%)، صفات جسديّة سلبيّة (25.14%)، صفات اجتماعيّة إيجابيّة (18.64%)، حالات شعوريّة سلبيّة (11.86%)، صفات جسديّة إيجابيّة (7.62%)، حالات شعوريّة إيجابيّة (11.86%). كما قدَّم البحث نموذجاً موضّحاً لكيفيّة توظيف هذه الألفاظ والتّراكيب في تعلّيم العربيّة للنّاطقين بغيرها، والنّموذج موجّه لمتعلّمي المستوى المتوسط الأوسط في مهارة الكلام.